Randomized Trial of a Peer-Led, Telephone-Based Empowerment Intervention for Persons With Chronic Spinal Cord Injury Improves Health Self-Management - Houlihan, Bethlyn Vergo; Brody, Miriam; Everhart-Skeels, Sarah; Pernigotti, Diana; Burnett, Sam; Zazula, Judi; Green, Christa; Hasiotis, Stathis; Belliveau, Timothy; Seetharama, Subramani; Rosenblum, David; Jette, Alan (Archives of physical medicine and rehabilitation, 2017)
To evaluate the impact of “My Care My Call” (MCMC), a peer-led, telephone-based health self-management intervention in adults with chronic spinal cord injury (SCI). Single-blinded randomized controlled trial. General community. Convenience sample of adults with SCI (N=84; mean time post-SCI, 9.9y; mean age, 46y; 73.8% men; 44% with paraplegia; 58% white). Trained peer health coaches applied the person-centered health self-management intervention with 42 experimental subjects over 6 months on a tapered call schedule. The 42 control subjects received usual care. Both groups received the MCMC Resource Guide. Primary outcome—health self-management as measured by the Patient Activation Measure (PAM). Secondary outcomes—global ratings of service/resource use, health-related quality of life, and quality of primary care. Intervention participants averaged 12 calls over 6 months (averaging 21.8min each), with distinct variation. At 6 months, intervention participants reported a significantly greater change in PAM scores (6mo: estimate, 7.029; 95% confidence interval, .1018–13.956; P=.0468) compared with controls, with a trend toward significance at 4 months. At 6 months, intervention participants reported a significantly greater decrease in social/role activity limitations (estimate, −.443; P=.0389), greater life satisfaction (estimate, 1.0091; P=.0522), greater services/resources awareness (estimate, 1.678; P=.0253), greater overall service use (estimate, 1.069; P=.0240), and a greater number of services used (estimate, 1.542; P=.0077). Subgroups most impacted by MCMC on PAM change scores included the following: high social support, white persons, men, 1 to 6 years postinjury, and tetraplegic. This trial demonstrates that the MCMC peer-led, health self-management intervention achieved a positive impact on self-management to prevent secondary conditions in adults with SCI. These results warrant a larger, multisite trial of its efficacy and cost-effectiveness.